Young Women`` s Opinions about the Use of Cosmetics and Its Impact on Health - Gražina Šniepienė; Margarita Maniušienė; Judita Jonuševičienė; Geriuldas Žiliukas (Lithuanian Sports University, 2019)
Research background. Young women use cosmetic products daily to maintain a good aesthetic appearance and express their individuality. Their habits of use aﬀect not only their skin and hair condition but also their well-being and health. After getting familiar with the young women's opinion about the use of cosmetics, we aimed to promote women's interest in the safe use of cosmetics. The aim of the study was to assess the opinions of young women towards the use of cosmetics. Methods. Quantitative research, questionnaire method was applied. The study sample consisted of students of the Klaipeda University of Applied Sciences studying in the feld of biomedicine (girls and women, n = 240). Results. The study showed that the most commonly used were hygiene products. Most respondents used between 5 and 10 cosmetic products per day (39.6%). The main choice criteria of cosmetic products were as follows: benefcial long-term eﬀects and the desired eﬀect on beauty. More than 90% of young women believed that cosmetic products might contain substances that were harmful to health, but about 36% of them asked about the presence of specifc substances. Conclusion. The study showed that young women's habits posed a certain risk of adverse eﬀects, as a large number of them were not interested in the composition of the product before purchasing. Despite the fact that the majority of women experienced side eﬀects, a few of them performed a patch test. Most women agreed that it was worth buying organic, though more expensive cosmetics, but a small number applied it themselves. Keywords: cosmetics, women, opinion.